Análise da produção escrita em tarefas de exploração-investigação matemática em um 4º ano do Ensino Fundamental - Souza, Luciana de (2021)
This research was based on assessing for learning and mathematical investigation in classroom approaches for teaching Mathematics in the early years of Elementary School. More specifically, the subject is the analysis of elementary school students writing productions in assessments involving mathematical exploration-investigation, considering evaluation as an investigation process and as an opportunity to learn. The research was conducted around the following question: Which ways do 4th-year students use to solve mathematical tasks that involve exploration-investigation? The objective was to understand more about the way this group of students solved such tasks. The objective was to understand more about how this group of students handles such tasks. This is qualitative and interpretative research based in the content analysis as a tool to understand information obtained. In order to build data, six exploratory investigative assessments were elaborated and applied. The analysis of the writing production of the first assessment provided description, interpretation, and inferences used to identify and understand the way students solved such tasks, patterns were separated. Based on that analysis, some interventions were realized in the classroom taking into consideration how students handle the tasks, the second assessment was realized and so on until the sixth In this research it was noted that students handle tasks both in conventional and in idiosyncratic ways. Students that handled tasks in an idiosyncratic way occasionally chose the conventional approach as well. Besides that, it was observed that even when a Hypothetical Investigation Trajectory - HIT was provided by the teacher, students may not engage with the investigative task, remaining to the task only its exploratory intent. This research intends to inspire other professionals to study and to put the exploration-investigation mathematical assessments into practice in the classroom and/or to use writing production analysis as an alternative for evaluation as an investigation practice aiming a learning-oriented evaluation and to provide theoretical and methodological support for teaching Mathematics in the early years of Elementary School. This paper also ponders that more studies describing the integration between mathematical investigation and writing production analysis are necessary as well as others correlating these approaches with other tendencies aiming at a quality education in mathematical education.